Outcomes of adolescents and young adults treated for brain and skull base tumors with pencil beam scanning proton therapy. Issue 12 (2nd September 2020) - Lim, Pei S.; Tran, Sébastien; Kroeze, Stephanie G.C.; Pica, Alessia; Hrbacek, Jan; Bachtiary, Barbara; Walser, Marc; Leiser, Dominic; Lomax, Antony J.; Weber, Damien C.
Abstract: Background: The use of proton therapy (PT) in adolescents and young adults (AYAs) is becoming increasingly popular. This study aims to assess the outcomes and late toxicity consequences in AYAs (15‐39 years) with brain/skull base tumors treated with pencil beam scanning proton therapy. Methods: One hundred seventy six AYAs treated curatively at the Paul Scherrer Institute (PSI) were identified. Median age was 30 years (range 15‐39) and median prescribed dose was 70.0 Gy (relative biological effectiveness [RBE]) (range 50.4‐76.0). The most common tumors treated were chordomas/chondrosarcomas (61.4%), followed by gliomas (15.3%), and meningiomas (14.2%). Results: After a median follow up of 66 months (range 12‐236), 24 (13.6%) local only failures and one (0.6%) central nervous system (CNS) distant only failure were observed. The 6‐year local control, distant progression‐free survival, and overall survival were 83.2%, 97.4%, and 90.2%, respectively. The 6‐year high‐grade (≥grade [G] 3) PT‐related late toxicity‐free survival was 88.5%. Crude late toxicity rates were 26.2% G1, 37.8% G2, 12.2% G3, 0.6% G4, and 0.6% G5. The one G4 toxicity was a retinopathy and one G5 toxicity was a brainstem hemorrhage. The 6‐year cumulative incidences for any late PT‐related pituitary, ototoxicity, and neurotoxicity were 36.3%, 18.3%, and 25.6%; whilst high‐grade (≥G3) ototoxicity and neurotoxicity were 3.4% and 2.9%, respectively. No secondary malignancies were observed. The rate of unemployment was 9.5% pre‐PT, increasing to 23.8% post‐PT. Sixty‐two percent of survivors were working whilst 12.7% were in education post‐PT. Conclusions: PT is an effective treatment for brain/skull base tumors in the AYA population with a reasonable late toxicity profile. Despite good clinical outcomes, around one in four AYA survivors are unemployed after treatment.